2019
DOI: 10.1093/ndt/gfz135
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal adaptation in potassium-depleted men: role of progesterone?

Abstract: Background In rodents, the stimulation of adrenal progesterone is necessary for renal adaptation under potassium depletion. Here, we sought to determine the role of progesterone in adrenal adaptation in potassium-depleted healthy human volunteers and compared our findings with data collected in patients with Gitelman syndrome (GS), a salt-losing tubulopathy. Methods Twelve healthy young men were given a potassium-depleted die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Another study has the intervetion of progesterone to alleviate the hypokalemia (NCT02297048). In line with this hypothesis, Blanchard et al [ 197 ] have reported that adrenal glands adapt their response to levels of hypokalemia and hyponatremia. This could be the first step towards a better understanding of the pathophysiology and, perhaps, towards a new therapeutic group.…”
Section: Therapeutic Approachesmentioning
confidence: 83%
“…Another study has the intervetion of progesterone to alleviate the hypokalemia (NCT02297048). In line with this hypothesis, Blanchard et al [ 197 ] have reported that adrenal glands adapt their response to levels of hypokalemia and hyponatremia. This could be the first step towards a better understanding of the pathophysiology and, perhaps, towards a new therapeutic group.…”
Section: Therapeutic Approachesmentioning
confidence: 83%
“…In parallel, the consumption of salt (NaCl) and potassium (K + ) have been completely modified, switching from a rich-K + /low NaCl diet in the hunter-gatherer population to the opposite in the modern, westernized population (2). In a recent study, we showed that the median daily Na + and K + intakes in young Parisian males are 136 mmol and 57 mmol/day, respectively (3) which are far from the recommended values by the dietary reference intakes (maximal Na + intake 65 mmol/day and minimal K + intake 120 mmol/day). Fortunately, we have the ability to cope with these changes that occurred very recently in our eating habits thanks to our kidneys.…”
Section: Introductionmentioning
confidence: 86%
“…The samples used to measure urine GDF15 were described previously in (3). Briefly, The healthy volunteers were Caucasian males 18 to 35 years of age.…”
Section: Human Urine Samplesmentioning
confidence: 99%
“…One such mechanism is circadian rhythms which are known to impact secretion of hormones (such as ALD) as well as impact renal function [42][43][44][45]. To incorporate circadian rhythms, some model parameters, e.g., F GFR , would need to be made time dependent Progesterone has also shown to play a role in K + regulation in both males and females [46,47]. Future work may study the impact of other regulatory mechanisms, as these mechanisms become better characterized by new experimental data.…”
Section: Model Limitations and Future Workmentioning
confidence: 99%